Mindfulness among lebanese university students and its indirect effect between mental health and wellbeing - Zeinab Bitar; Radosław Rogoza; Souheil Hallit; Sahar Obeid (BMC Psychology, 2023)
Abstract Background University students are a high-risk population for developing mental health issues. Mindfulness, the non-judgmental awareness of the present moment, has an effective role in numerous psychological contexts among students. However, no previous studies have investigated the association between mindfulness, mental health and wellbeing among Lebanese university students. Therefore, this study aimed to assess the mediating effect of mindfulness in the association between mental health and wellbeing in this population. Methods This cross-sectional study enrolled 363 Lebanese university students recruited through convenience sampling (July-September 2021). The Wellbeing Index Scale, Lebanese Anxiety Scale, Patient Health Questionnaire and Freiburg Mindfulness Inventory were used to assess subjective well-being, anxiety, depression and mindfulness respectively. Results Our findings showed that higher mindfulness (Beta = 0.18; p < 0.001) was significantly correlated with a higher wellbeing, whereas more depression (Beta=-0.36; p < 0.001) was significantly associated with a lower wellbeing. The results of the indirect effect analysis showed that mindfulness mediated the association between anxiety and wellbeing and between depression and wellbeing. Higher anxiety/depression were significantly associated with lower mindfulness and a lower wellbeing (direct effect). Moreover, higher mindfulness was significantly associated with a higher wellbeing. Conclusion Mindfulness is associated with improved wellbeing and plays an indirect role between mental health issues and wellbeing. Our results suggest that mindfulness presents an adaptive approach and coping method associated with improved students’ wellbeing.